The diagnostic value of trichoscopy in systemic sclerosis - Kwiatkowska, Małgorzata (J Dermatol Case Rep, 2016)
BACKGROUND/OBJECTIVES: Systemic sclerosis is a connective tissue disease, which is characterized by fibrosis of the skin and internal organs, presence of specific antibodies and vascular involvement. Capillaroscopy is a useful method for the diagnosis and follow-up of patients with systemic sclerosis. Trichoscopy is a rapid, non-invasive technique, which has become a standard procedure in differential diagnosis of scalp and hair diseases. The aim of this study was to assess whether trichoscopy may be applied in imaging microvessels in patients with systemic sclerosis. METHODS: The study included 17 patients with systemic sclerosis, and 31 healthy patients. In every patient 10 trichoscopy images were taken with Fotofinder II. RESULTS: In patients with systemic sclerosis trichoscopy of the frontal scalp area revealed polymorphic microvessels in 64,7% of patients, spider vessels (76,4%), capillary loops (52,9%), arborising vessels (41,1%) and avascular areas (35,2%). In healthy individuals these features were observed in polymorphic microvessels 6,4% of patients, spider vessels 6,4%, capillary loops 100%, arborising vessels 16,1%, avascular areas 9,6%, respectively. CONCLUSIONS: In conclusion, the presence of polymorphic vessels in frontal area in trichoscopy is characteristic for systemic sclerosis.